2011
DOI: 10.1590/s0101-28002011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of lipid and glucose metabolism biomarkers in non-diabetic hemodialysis and peritoneal dialysis patients

Abstract: ResumoObjetivo: O presente estudo foi desenhado pra investigar e comparar biomarcadores do metabolismo de glicose e lipídeos em pacientes não diabéticos em diálise peritoneal e hemodiálise. Métodos: O estudo possui um desenho prospectivo e transversal. Participantes: foram incluídos todos os pacientes prevalentes em terapia de substituição renal tratados em uma clíni-ca universitária. Intervenções: não houve intervenções. Medida das variáveis principais: as amostras de sangue foram coletadas com jejum oral de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…There is a debate and no consensus about the cut-off value of HOMA-IR in ESRD patients. However, de Moraes et al showed that the median level of HOMA-IR was 1.68 in HD patients [27]. This is in accordance with the median HOMA-IR value of our study.…”
Section: Discussionsupporting
confidence: 93%
“…There is a debate and no consensus about the cut-off value of HOMA-IR in ESRD patients. However, de Moraes et al showed that the median level of HOMA-IR was 1.68 in HD patients [27]. This is in accordance with the median HOMA-IR value of our study.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, involving both diabetic and nondiabetic PD patients, high glucose load was associated with poor survival 20 . As PD patients showed greater longitudinal increase in visceral fat and poorer glucose metabolism relative to HD patients 7 32 , our preliminary hypothesis was that glucose load related to PD fluid would affect survival by inducing visceral fat accumulation and aggravating insulin resistance. However, our data showed that neither glucose load nor PD duration was associated with VFA or HbA1c ( Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…104,108 This section is focused on nonconventional cardiovascular risk factors, with emphasis on modification by treatment with PD ( Figure 4). [111][112][113][114][115][116][117] Yet, the evidence that they translate into significantly worse outcomes for PD patients is variable. 109,110 Importance of Metabolic Risk Factors and the Role of Glucose-Sparing Regimens The most obvious risk factors exacerbated by PD are metabolic, related to systemic glucose absorption from the dialysate.…”
Section: Cardiovascular Risk Modification In Pd Patientsmentioning
confidence: 99%